Penerimaan Diri pada Orang Tua yang Memiliki Anak Tunagrahita Sedang di SLB Negeri Kota Pagaralam - Deva Agustini; Rina Oktaviana (Lembaga Teewan Journal Solutions, 2026)
This study aimed to explore the self-acceptance of parents who have children with moderate intellectual disabilities at the State Special Needs School in Pagaralam City. This research employed a qualitative approach using a phenomenological method. The participants consisted of parents of children with moderate intellectual disabilities enrolled at the State Special Needs School in Pagaralam City. Data were collected through in-depth interviews, observations, and documentation. The data were analyzed using the interactive model of Miles and Huberman, including data reduction, data display, and conclusion drawing. The findings revealed that parents experienced a gradual process of self-acceptance, beginning with feelings of shock, sadness, disappointment, and difficulty accepting their child's condition, before eventually accepting it as part of their lives. Self-acceptance was influenced by several factors, including family support, social support, religious beliefs, the adaptation process over time, and parental responsibility. Adequate social support and positive meaning-making helped parents reduce emotional distress, accept their children's condition more realistically, and provide more positive and optimal parenting. Therefore, self-acceptance among parents of children with moderate intellectual disabilities is a dynamic process influenced by both internal and external factors.